Agrobiznes na rzecz zrównoważonego rozwoju obszarów wiejskich - Kapusta, Franciszek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The concept of agribusiness emerged in the fifties of the 20th century and that of sustainable development at the beginning of the seventies. The agribusiness concept poses circumstances to harmonious development of activities producing goods meeting various human needs and in the same time contributing to sustainable development in rural areas. Separation of agribusiness in the framework of national economy allows to distinguish three areas: planning, organizational, and analytical. The whole subsystem - agribusiness - is functioning thanks to agriculture which is a basic element of rural areas. Moreover, large variety of the rural areas environment, and especially its resources with large and of improving quality work force is helping in running multipurpose activities. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 15-21